2017
DOI: 10.1021/acs.jctc.7b00555
|View full text |Cite
|
Sign up to set email alerts
|

Role of Exact Exchange and Relativistic Approximations in Calculating 19F Magnetic Shielding in Solids Using a Cluster Ansatz

Abstract: Calculations of F magnetic shielding in various materials are presented. In calculations on gas-phase molecules, the variation of magnetic shielding with the amount of Hartree-Fock exchange (HFX) in the functional demonstrates that excellent agreement with experiment is obtained with an admixture of 50%, here denoted PBE0 (50%). Calculations at the PBE, PBE0 (25%), and PBE0 (50%) levels on 10 crystalline organofluorines and 15 crystalline inorganic fluorides, in which a cluster ansatz is used to model the latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 113 publications
(276 reference statements)
3
43
0
Order By: Relevance
“…It should also be noted, that periodic structure calculations do not yield better agreement with experiment, and large cluster calculations using appropriately constructed symmetryadapted molecular clusters and high level of theory appear to be necessary, as we have demonstrated previously for fluorine in a wide variety of environments. 27…”
Section: Methodsmentioning
confidence: 99%
“…It should also be noted, that periodic structure calculations do not yield better agreement with experiment, and large cluster calculations using appropriately constructed symmetryadapted molecular clusters and high level of theory appear to be necessary, as we have demonstrated previously for fluorine in a wide variety of environments. 27…”
Section: Methodsmentioning
confidence: 99%
“…In the previous benchmarking study [182], hybrid functionals give a shift/shielding fitting gradient for 19 F that was significantly closer to the expected -1. A follow-up study [184] showed that increasing the fraction of Hartree-Fock exchange to 50% (compared to 25% in PBE0) further improved the regression slope, although the RMSDs (not calculated) did not seem to significantly improve. This is consistent with the idea the systematic limitations of DFT are often due to "self-interaction / delocalisation" errors [84] associated with the exchange energy correlation functional, which are reduced by decreasing the contribution of the PBE functional.…”
Section: Limitations Of Current Dft Functionalsmentioning
confidence: 97%
“…In this context, Dybowski and co-workers have identified that such discrepancies arise in DFT calculations of 19 F magnetic shielding. 75 …”
Section: Results and Discussionmentioning
confidence: 99%